Psychological and Pedagogical Vectors of Distance Learning in Higher Education: A Framework for Integrated Management and Support - Barbashova, Iryna; et al. (European Journal of Social Science Education and Research, 2025)
The proliferation of distance education in higher education (HE) offers unprecedented flexibility but simultaneously introduces significant challenges, including student isolation, disengagement, and diminished well-being, which adversely affect academic performance and retention. This paper addresses the critical need for a holistic support system that transcends traditional, siloed approaches. Using an integrative review methodology, this study synthesizes empirical and theoretical literature to develop a conceptual framework for integrating psychological and pedagogical support within digital learning environments. The framework emphasizes the synergistic relationship between fostering a sense of belonging, promoting student engagement, and providing accessible well-being counseling. We argue that a sense of belonging is a foundational element that mitigates negative psychological outcomes, such as anxiety, and enhances academic motivation. The proposed framework advocates for embedding well-being support directly into digital education platforms, creating a cohesive ecosystem that facilitates student success. By systematically combining psychological and pedagogical strategies, institutions can create a more resilient, supportive, and effective online learning experience. This paper offers a practical model for HE administrators and educators to guide the design and implementation of integrated support systems tailored for the digital age.
Keywords: distance learning, higher education, student engagement, sense of belonging, well-being counseling, integrated support framework, digital pedagogy